Students’ Perception of Google Translate in Online English Learning - Khusnul Khotimah; Wawan Wahyudin; Tatu Siti Rohbiah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2021)
The aim of this study is to find out the students’ perception of Google Translate in online English learning. The formulation problem of this study is how are the students’ perception of Google Translate as translation tool in online English learning process? This research was conducted through survey method. The participants of this study were 4th semester students who taken Translation class in English Education Departement, Faculty of Education and Teachers Training, Universitas Islam Negeri Sultan Maulana Hasanuddin Banten. The data of students’ perception of Google Translate as translation tool in online English learning were obtained by questionnaire and interview. The results of this study indicate that students give a positive perception of Google Translate as translation tool in learning English. The statement that gets the most answers are Agree with the result of the data is 28.86%. The positive assessment of the respondents come from their experience in learning English by using Google Translate. They are greatly helped in the learning process when the lecturer asks and explains the material about the translation. Since they do not know the meaning, they immediately consult to the Google Translate. This research also reveals that Google Translate is very useful for students to enhance new vocabularies. They, nevertheless, still pay attention to the results of the translation from Google Translate by looking at the word equivalence, accuracy, and uncluttered sentence structure.